Assessing the Prerequisite of Successful CSR Implementation: Are Consumers Aware of CSR Initiatives? - Pomering, Alan (Journal of business ethics, 2009)
As a reflection of the values and ethics of firms, corporate social responsibility (CSR) has received a large amount of research attention over the last decade. A growing area of this research is the CSR–consumer relationship. Results of experimental studies indicate that consumer attitudes and purchase intentions are influenced by CSR initiatives – if consumers are aware of them. In order to create this awareness, business is increasingly turning to ‹pro-social’ marketing communications, but such campaigns is met with scepticism and their effectiveness are therefore uncertain. Consequently, researchers in the field (for example, Maignan, 2001; Mohr et al., 2001) have called for empirical studies to determine the level of actual consumer awareness of CSR initiatives. This study examines the Australian banking sector, which engages in and promotes its CSR activities, to help fill this gap. Results from our qualitative study with bank managers, and our quantitative study with consumers, indicate low consumer CSR awareness levels. Consumer understanding of many of the social issues banks engage with is also low. While CSR is effective in eliciting favourable consumer attitudes and behaviour in theory, CSR has not proven its general effectiveness in the marketplace. The low consumer awareness of the various social issues in which firms engage with their CSR programs suggests that firms may need to educate consumers, so they may better contextualise CSR initiatives communicated. However, better context may amount to little if claimed CSR initiatives are perceived as inconsistent with other facets of the business that reflect its values and ethics.